2010
DOI: 10.1163/156853810791769446
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity in Chinese alligator (Alligator sinensis) clutches during a reproductive season at Xuanzhou Nature Reserve

Abstract: Paternity testing was determined in Chinese alligator (Alligator sinensis) clutches during a reproductive season at Xuanzhou Nature Reserve, using five microsatellite loci. DNA from ten mother and offspring clutches was analysed to identify paternal alleles. Three or four paternal alleles were observed among three of ten clutches. These clutches were sired by at least two different males. This present study confirmed the effectiveness of microsatellite DNA markers in detecting multiple paternity within natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Crocodilians, which have widely varying population densities and degrees of male territoriality, provide an excellent system to explore the evolutionary and ecological drivers that underlie the observed variation in the frequency of multiple paternity (Amavet, Rosso, Markariani, & Piña, 2008;Budd, Spotila, & Mauger, 2015;Davis, Glenn, Elsey, Dessauer, & Sawyer, 2001;Lance et al, 2009;Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013;Mcvay et al, 2008;Muniz et al, 2011;Ojeda, Amavet, Rueda, Siroski, & Larriera, 2017;Oliveira, Marioni, Farias, & Hrbek, 2014;Lafferriere et al, 2016;Wu & Hu, 2010). The frequency of multiple paternity observed across crocodilian taxa ranges from 32% in the Chinese alligator (Alligator sinensis) to 100% in black caiman (Melanosuchus niger) (Muniz et al, 2011;Wu & Hu, 2010). Among crocodilians, it is not clear if the frequency of multiple paternity is driven by population density and/or mate encounter rate (Amavet et al, 2008;Budd et al, 2015;Davis et al, 2001;Lance et al, 2009;Lewis et al, 2013;McVay et al, 2008;Muniz et al, 2011;Oliveira et al, 2014;Lafferriere et al, 2016;Wu & Hu, 2010) though both have been suggested (Budd et al, 2015;Lafferriere et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crocodilians, which have widely varying population densities and degrees of male territoriality, provide an excellent system to explore the evolutionary and ecological drivers that underlie the observed variation in the frequency of multiple paternity (Amavet, Rosso, Markariani, & Piña, 2008;Budd, Spotila, & Mauger, 2015;Davis, Glenn, Elsey, Dessauer, & Sawyer, 2001;Lance et al, 2009;Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013;Mcvay et al, 2008;Muniz et al, 2011;Ojeda, Amavet, Rueda, Siroski, & Larriera, 2017;Oliveira, Marioni, Farias, & Hrbek, 2014;Lafferriere et al, 2016;Wu & Hu, 2010). The frequency of multiple paternity observed across crocodilian taxa ranges from 32% in the Chinese alligator (Alligator sinensis) to 100% in black caiman (Melanosuchus niger) (Muniz et al, 2011;Wu & Hu, 2010). Among crocodilians, it is not clear if the frequency of multiple paternity is driven by population density and/or mate encounter rate (Amavet et al, 2008;Budd et al, 2015;Davis et al, 2001;Lance et al, 2009;Lewis et al, 2013;McVay et al, 2008;Muniz et al, 2011;Oliveira et al, 2014;Lafferriere et al, 2016;Wu & Hu, 2010) though both have been suggested (Budd et al, 2015;Lafferriere et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of multiple paternity observed across crocodilian taxa ranges from 32% in the Chinese alligator (Alligator sinensis) to 100% in black caiman (Melanosuchus niger) (Muniz et al, 2011;Wu & Hu, 2010). Among crocodilians, it is not clear if the frequency of multiple paternity is driven by population density and/or mate encounter rate (Amavet et al, 2008;Budd et al, 2015;Davis et al, 2001;Lance et al, 2009;Lewis et al, 2013;McVay et al, 2008;Muniz et al, 2011;Oliveira et al, 2014;Lafferriere et al, 2016;Wu & Hu, 2010) though both have been suggested (Budd et al, 2015;Lafferriere et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From Table 1, when the total number of alleles for each crocodilian parentage analysis study are tallied, the number of alleles varies from 24 (Amavet et al, 2012; Hu & Wu, 2010) to 91 alleles (Oliveira et al, 2014) with an average of 42 total alleles equivalent to the 5H panel used herein. Following from the findings in this study and given that nest assignment is possible in crocodilians if offspring are being sampled from eggs/embryos, when fewer alleles are available, using GERUD 2.0 or the SLMM is sufficient to accurately infer sire number.…”
Section: Discussionmentioning
confidence: 99%
“…Understandably, it is not always possible or safe to take a tissue or blood sample from any adult crocodilian. However, at the very least, maternal DNA was successfully extracted from the membrane of unfertilized eggs in the Chinese alligator ( Alligator sinensis ; Hu & Wu, 2010), fetal membranes of the Nile crocodile ( Crocodylus niloticus ; Nöthling et al, 2020), and from the eggshell matrix in birds (e.g., Egloff et al, 2009). Extraction of environmental DNA (eDNA) from soil samples in direct contact with the eggs when the nest is opened may also be a useful source of maternal DNA (Adams et al, 2019) from mucous residue which is present on eggs at the time of oviposition.…”
Section: Discussionmentioning
confidence: 99%